Spontaneous Mediastinal Hemorrhage Secondary to Oral Anticoagulation - Mazziotti, Alexander (1986)
We report a rare case of spontaneous mediastinal hemorrhage secondary to appropriate oral anticoagulation in an otherwise healthy 35-year-old woman. This case was unique in view of the patient's age and the fact that she had no underlying pathologic condition. Although the literature describes only two other cases of spontaneous mediastinal hemorrhage secondary to oral anticoagulant therapy alone, such bleeding has also been observed in patients on combined oral anticoagulant and fibrinolytic therapy and on heparin therapy. Therefore, this kind of hemorrhage should be included in the differential diagnosis of chest pain in such patients. The diagnosis is confirmed by chest X-ray films, computer tomographic scanning, and digital angiography. Supportive treatment is usually sufficient, since tamponade tends to intervene before cardiac compromise can occur. (Texas Heart Institute Journal 1986; 13:333-336)